The queen, the princes & the mermaid : Hans Christian Andersen's most enchanting tales - Andersen, H. C. (Hans Christian), 1805-1875 (Pushkin Children's, 2020)
Contains five illustrated fairy tales by Hans Christian Andersen. First, a girl embarks on a dangerous journey to save her friend from the Snow Queen. Then, an emperor thinks a mechanical bird's song is more beautiful than a real Nightingale but when the bird breaks down, the Nightingale returns. Finally, a mermaid dreams of becoming human.